2020
DOI: 10.1002/isaf.1480
|View full text |Cite
|
Sign up to set email alerts
|

A neural‐network‐based decision‐making model in the peer‐to‐peer lending market

Abstract: Summary This study proposes an investment recommendation model for peer‐to‐peer (P2P) lending. P2P lenders usually are inexpert, so helping them to make the best decision for their investments is vital. In this study, while we aim to compare the performance of different artificial neural network (ANN) models, we evaluate loans from two perspectives: risk and return. The net present value (NPV) is considered as the return variable. To the best of our knowledge, NPV has been used in few studies in the P2P lendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Hu et al [20] research the performance, financing difficulty, and financing cost of the peasantry and low-income people on the Renrendai platform by combining inclusive finance and online loans. Babaei and Bamdad [21] have evaluated the return and risk of the P2P item using Artificial Neural Network and Logistic function, respectively.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Hu et al [20] research the performance, financing difficulty, and financing cost of the peasantry and low-income people on the Renrendai platform by combining inclusive finance and online loans. Babaei and Bamdad [21] have evaluated the return and risk of the P2P item using Artificial Neural Network and Logistic function, respectively.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The return and risk of a new loan can be estimated as the similarity weighted average of returns and risks of the other loans. The same approach has been used by Chi et al (2019) and Babaei and Bamdad (2020a, 2020b), for example, and was found to overperform grade‐based similarity in all the cases. As an alternative, Ding, Cheng, and Jiang (2020) utilized graph theory and constructed bipartite graphs based on the data collected from a P2P platform.…”
Section: Background and Literature Reviewmentioning
confidence: 68%
“…The fundamental problem of the above two contradictions is the personalized recommendation problem of the mobile digital library. Mobile digital libraries' personalized recommendation is to process information such as readers' interests and knowledge fields into knowledge elements that can vividly describe readers' preferences [1]. This supports various recommendation services of the digital library.…”
Section: Introductionmentioning
confidence: 81%